PENYULUHAN HUKUM TERHADAP PENGATURAN NIKAH SIRI DI DALAM SISTEM HUKUM DI INDONESIA - Munajah Munajah; Yati Nurhayati; Muthia Septarina; Nahdhah (Scholar Center, 2021)
Community service at Pondok Tahfidz Madinatul Qur'an Banjarmasin which is aimed at the students of Pondok Tahfidz, aims to provide knowledge of the legal consequences arising from unregistered marriages. Lack of knowledge about the consequences of unregistered marriages is the main factor in the many practices of unregistered marriages that occur in society. This community service entitled